Technological support to foster students’ learning experience in electrical measurement class: A mobile learning-based hypermedia approach - Hamid, Mustofa Abi; Nurtanto, Muhammad; Desmira; Setiawan, Dedi; Hakiki, Muhammad; Fadli, Radinal (2024)
This study aims to develop hypermedia products based on mobile learning to serve as instructional tools for the Electrical Measurement course. This study employs a Research and Development (R&D) approach utilizing the ADDIE development model, which encompasses Analysis, Design, Development, Implementation, and Evaluation. Data collection was conducted through interviews, questionnaires, and observation methods in the Electrical Measurement class. The study employed a nonprobability sampling technique, involving 30 respondents from the Department of Electrical Engineering Vocational Education, including media experts and material experts. The research findings indicate that the feasibility of learning media, as evaluated by media experts, received an average score of 90, categorizing it as “very feasible.” Material experts assessed the feasibility with an average score of 94, also placing it in the “very feasible” category. Additionally, the feasibility regarding the use of learning media was scored at 78.1, which is similarly classified as “very feasible.” Mobile learning-based hypermedia can enhance the learning experience of students in electrical measurement courses.